1991
DOI: 10.2323/jgam.37.519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metal cations on chromate reduction by enterobacter cloacae strain hol.

Abstract: Wastewaters containing hexavalent chromium (chromate: Cr042 ) are generated in many industrial processes, including chromium plating, metal cleaning and processing, wood preservation, and alloy preparation (6). Since Cr042 is harzardous to fauna and flora in natural ecosystems, these wastewaters must be treated before being discharged into the environment (7,8,10,11).In our previous studies (2, 4, 5, 9), we demonstrated the potential of a chromate-reducing bacterium, Enterobacter cloacae (strain HO 1), to remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…However, similar results indicating the strong inhibition caused by heavy metal cations on the reduction of chromate were reported by Hardoyo et al (1991) for anaerobically grown E. cloacae. B. subtilis cells appear to be significantly more resistant to the presence of these metal cations, as derived from the lower values of percent inhibition of chromate reduction found in our studies in comparison with those reported by Hardoyo et al (1991).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…However, similar results indicating the strong inhibition caused by heavy metal cations on the reduction of chromate were reported by Hardoyo et al (1991) for anaerobically grown E. cloacae. B. subtilis cells appear to be significantly more resistant to the presence of these metal cations, as derived from the lower values of percent inhibition of chromate reduction found in our studies in comparison with those reported by Hardoyo et al (1991).…”
supporting
confidence: 72%
“…In fact, to our knowledge, there is only one report published as to the effects of heavy metals on the anaerobic reduction of chromate by Gram-negative Enterobacter cloacae (Hardoyo et al, 1991). Here, we report for the first time, the effect of the most common heavy metal cations found in chromate-bearing wastewaters on chromate reduction by the aerobic Gram-positive bacterium Bacillus subtilis.…”
mentioning
confidence: 77%
“…GARBISU et al [45] showed that Cr(VI) reduction in cell suspensions of Bacillus subtilis was inhibited by Cd 2+ , Cu 2+ , Zn 2+ and Ni 2+ . Similar results were obtained in studies using anaerobically grown cells of Enterobacter cloacae [46]. In conclusion, S. oneidensis-mediated Cr(VI) reduction has been demonstrated under a variety of environmentally relevant conditions.…”
Section: Discussionsupporting
confidence: 76%
“…The high optimum temperature suggests that the bacterium should be useful in a tropical climate like Malaysia where normal soil temperatures could reach as high as 35 °C (Sinnakkannu et al 2004). In other similar works on the biological reduction of Cr(VI), the requirement of near-neutral pH and a moderate temperature range is shared by many chromate-reducing bacteria (Horitsu et al 1978;Gvozdyak et al 1986;Hardoyo et al 1991;Rege et al 1997;Koósz et al 2008).…”
Section: Resultsmentioning
confidence: 94%